Potential use of green algae Caulerpa lentillifera as feed ingredient in the diet of Nile tilapia Oreochromis niloticus - Putri, Nadisa Theresia; Jusadi, Dedi; Setiawati, Mia; Sunarno, Mas Tri Djoko (Jurnal Akuakultur Indonesia, 2017)
ABSTRACT The high composition of import raw material of fish diet in Indonesia causes feed price expensively and should be replaced using local materials such as green macro algae. It is, therefore, this study aimed to evaluate effect of diet containing the Caulerpa lentillifera, as feed ingredient in the diet of Nile tilapia Oreochromis niloticus. This study consisted of two experiments which were C. lentillifera digestibility test for raw material feed for tilapia and growth performance test of tilapia. C. lentillifera digestibility test was done by using Cr2O3 as indicators and analysis of faecal tilapia. The second experiment is growth performance test using a completely randomised design with four diets were formulated at variuos rates of C. lentillifera meal of 0 (control), 10, 20, and 30%. A number of 240 tilapia fingerlings of 3.41±0.10 g in mean weight were randomly stocked in 12 aquaria and fed on diet test for growth performanced of rearing period. C. lentillifera digestiility test result showed a good value as a raw material feed tilapia, the digestibility of C. lentiliifera and protein digestibility amounted to 68.81% and 86.31%. Growth performance parameters showed the use of 10% and 20% is not significantly different from the control (P>0.05), to the final body weight, protein efficiency ratio, protein retention, specific growth rate, and feed efficiency. But, the diet test at 30% performed the lowest growth performance and feed utilization as well of tilapia fingerlings. This study, therefore, concludes that C. lentillifera meal could be used up to 20% in the tilapia diet. Keywords: Caulerpa lentillifera, Nile tilapia, feed utilization, growth performance  ABSTRAK Tingginya jumlah bahan baku impor dalam pakan ikan di Indonesia menyebabkan harga pakan yang tinggi dan harus diganti menggunakan bahan alternatif lokal seperti makro alga. Penelitian ini bertujuan untuk mengkaji pengunaan dari pakan yang mengandung Caulerpa lentillifera sebagai bahan baku pakan ikan nila Oreochromis niloticus. Tahapan penelitian terdiri atas uji kecernaan C. lentillifera sebagai bahan baku dan uji kinerja pertumbuhan ikan nila. Metode uji kecernaan menggunakan Cr2O3 sebagai indikator pakan dan analisis feses ikan nila. Tahap penelitian kedua adalah kinerja pertumbuhan menggunakan rancangan acak lengkap dengan pakan diformulasikan dengan inklusi 0 (kontrol), 10, 20, dan 30% tepung C. lentillifera. Ikan nila sebanyak 240 ekor, dengan berat rata-rata 3,41±0,1g dibagi kedalam 12 akuarium dan diberi pakan perlakuan untuk melihat kinerja pertumbuhan. Hasil uji kecernaan C. lentillifera menunjukkan nilai yang baik sebagai bahan baku pakan ikan nila, yaitu kecernaan bahan sebesar 68,81% dan kecernaan protein sebesar 86,31%. Parameter kinerja pertumbuhan menunjukkan perlakuan penambahan 10% dan 20% tepung C. lentillifera tidak berbeda nyata (P>0,05) dengan kontrol, yang terdiri atas: bobot tubuh akhir, pertumbuhan mutlak, protein efisiensi rasio, retensi protein, laju pertumbuhan spesifik dan efisiensi pakan. Namun, pakan perlakuan 30% menghasilkan kinerja pertumbuhan dan efisiensi pakan yang lebih rendah pada ikan nila. Penelitian ini memberikan hasil, penggunaan tepung C. lentillifera dapat digunakan sampai 20% dalam pakan ikan nila.   Kata kunci: Caulerpa lentillifera, nila, pemanfaatan pakan, kinerja pertumbuhan